Electro hydraulic control theory and its applications under extreme environment - Yin, yaobao; Wu, Jiangwei (Butterworth-Heinemann, an imprint of Elsevier, 2019)
Electro hydraulic Control Theory and Its Applications under Extreme Environment not only presents an overview on the topic, but also delves into the fundamental mathematic models of electro hydraulic control and the application of key hydraulic components under extreme environments. The book contains chapters on hydraulic system design, including thermal analysis on hydraulic power systems in aircraft, power matching designs of hydraulic rudder, and flow matching control of asymmetric valves and cylinders. With additional coverage on new devices, experiments and application technologies, this book is an ideal reference on the research and development of significant equipment.